Applicator and Primo Effects on the Persistence of Painted Golf Course Water Hazard and Out‐of‐Bounds Lines on Bermudagrass. Issue 1 (11th January 2014) - Fry, Jack D.; Kruse, Jason K.
Abstract : Paint applied as an aerosol has been the standard in marking water hazards and out‐of‐bounds lines on golf courses. Experiments were conducted in Citra, FL and Manhattan, KS to compare aerosol treatments to paint applied in bulk with a backpack applicator or sport field line applicator, with or without the inclusion of the growth regulator Primo (active ingredient trinexapac ethyl), for persistence of water hazard and out‐of‐bounds lines on bermudagrass. Regardless of applicator type, no water hazard or out‐of‐bounds line retained acceptable color intensity longer than 5 weeks. Applying red paint in bulk with Primo through the backpack sprayer or sport field line applicator resulted in lines that provided a lateral water hazard line of acceptable color intensity for about 16 and 8 days longer in Florida and Kansas, respectively, compared to aerosol‐applied paint. Likewise, white paint applied with Primo to mark out‐of‐bounds lines with a backpack applicator persisted about 6 days longer in Florida than that applied with an aerosol. Enhancing line intensity and persistence with bulk paint that is lower in price compared to aerosol paint, combined with Primo, may be of interest to golf course superintendents and others responsible for marking water hazard and out‐of‐bounds lines on golf courses.